Using dissolved noble gases to characterize the groundwaters of the Southern Portion of the Guarani Aquifer System at the Brazil-Uruguay Border Region - Gemeiner, Hendryk [UNESP]; Teramoto, Elias Hideo [UNESP]; Veroslavsky, Gerardo; Chang, Hung Kiang [UNESP] (Elsevier, 2025)
As one of the largest aquifers in the world, the Guarani Aquifer System (GAS) serves as a critical water resource for Brazil, Argentina, Paraguay, and Uruguay. Tracing the movement of groundwater is essential for reliable conceptual models to support its sustainable management. Because of its importance, several studies have been accomplished to understand the dynamics of GAS. However, some important aspects are not yet sufficiently understood. In order to improve the current understanding of GAS, this study presents data on dissolved gases obtained from a total of 27 groundwater wells, encompassing both the confined and unconfined sections of the southern GAS, along with its overlying and underlying aquifers, in the western border region of Brazil and Uruguay. Excess air values expressed as △Ne were relatively low and comparable between the unconfined and confined portion of the GAS, with values of 7.7 ± 6.1 % and 7.8 ± 6.7 %, respectively. Calculated mean noble gas temperature (NGT) for the confined portion of the GAS was slightly higher (22.6 ± 4.9 °C) than that of the unconfined portion (17.9 ± 2.0 °C), which is in conformity with the mean annual air temperature (MAAT) of the region. Elevated He concentrations and higher NGT values in wells from the confined GAS, located far from the recharge area, suggest recharge occurred before the Last Glacial Maximum (LGM). The significant variation of NGTs, along with existing water isotope data from the confined GAS, suggests potential mixing of these groundwaters from adjacent underlying or overlying aquifer systems.
Keywords: Excess-air; Groundwater mixing; Guarani Aquifer System; Noble gases; Paleotemperature